Performance Analysis of Students Through Critical Thinking Ability Based on Mathematic Ability - A’yun, Qurrota; Yanuarti, Rosita; Sujiwo, Dimas Anditha Cahyo (Malikussaleh Journal of Mathematics Learning (MJML), 2021)
The standard of critical thinking in this study, namely: first, interpretation is on a problem can showing / writing what they know and what is asked about the problem correctly; second, analysis is the activity of identifying the relationship between statements, questions and concepts in a problem through making mathematical models and accompanied by the right reasons; third, evaluation is the right strategy in solving problems and fourth, conclusion is accuracy in drawing conclusions from what is asked. While the type of research used is descriptive qualitative type. The instruments used were interview guidelines and test questions. The interview used is a structured interview and the test used in the form of a math problem test with derived application material consisting of 3 problem descriptions with material that has been received by students. Student performance levels in this study are at the Apprentice level and the Novice level. The acquisition of data at the Apprentice level the average value is different, this is because the acquisition of data on each indicator is different overall. This is because the subject is not accustomed to or accustomed to working on open questions or also problem stories / problems. Student performance levels in this study are at the Apprentice level and the Novice level. The acquisition of data at the Apprentice level the average value is different, this is because the acquisition of data on each indicator is different overall. This is because the subject is not accustomed to or accustomed to working on open questions or also problem stories/problems.